KEPEMIMPINAN DIGITAL MASA DEPAN MELALUI PENDIDIKAN KARAKTER GENERASI ALPHA [FUTURE DIGITAL LEADERSHIP THROUGH CHARACTER EDUCATION FOR THE ALPHA GENERATION] - Lastiar Roselyna Sitompul; Muhammad Japar; Moch Sukardjo; M.Helmi Azhar; Luthpi Saepuloh (Universitas Pelita Harapan, 2023)
AbstractThe Alpha generation is a unique generation, born in the era of digital technology. From an early age, they have been in contact with information technology. Based on previous research, this generation spends a lot of time in front of screens and is fluent in using technological tools. There is a negative impact of using technology when it is not accompanied by character education. As they are the future generation of leaders, teachers and parents must take an approach based on the characteristics of the Alpha generation in parenting and teaching to develop leadership character. This research aims to examine the characteristics of the Alpha generation, character education for the Alpha generation, and parenting styles that are effective in preparing to be the digital leaders. The research method is a literature study. The results of the literature study show that the Alpha generation has great potential as digital leaders in a digital environment and character education in schools and parental care must adapt to the characteristics of the Alpha generation by providing examples, mentoring, and good relationships.Bahasa Indonesia AbstrakGenerasi Alpha adalah generasi unik, lahir di era teknologi digital. Sejak usia dini, telah bersentuhan dengan teknologi informasi. Berdasarkan penelitian terdahulu generasi ini banyak menggunakan waktu di depan layar dan fasih dalam penggunaan alat-alat teknologi. Terdapat dampak negatif dari penggunaan teknologi yang tidak disertai dengan pendidikan karakter. Sebagai generasi pemimpin di masa depan, guru dan orang tua harus mempunyai pendekatan berdasarkan karakteritik generasi alpha dalam pola asuh dan pengajaran untuk mengembangkan karakter kepemimpinan. Penelitian bertujuan mengkaji karakteristik generasi Alpha, bagaimana pendidikan karakter untuk generasi Alpha dan pola asuh orang tua yang efektif dalam mempersiapkan kepemimpinan digital generasi Alpha. Metode penelitian adalah metode kepustakaan, melalui penelurusan literatur terpercaya. Hasil penelitian studi literatur menunjukkan generasi Alpha mempunyai potensi besar sebagai pemimpin digital melalui lingkungan digital yang telah dikuasai, pendidikan karakter di sekolah dan asuhan orang tua harus menyesuaikan dengan karakteristik generasi Alpha, dengan memberikan keteladanan, pendampingan, serta relasi yang baik.